Hudson Strait ice dam collapse: An explanation for the onset of the Younger Dryas cold climate in Europe in only one year - Johnson, Robert Glenn (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2021)
The Younger Dryas cold climate event in Europe began abruptly at about 12,679 years BP. The abruptness of the onset was caused by the rapid collapse of a dynamic ice dam that had existed because of ice stream flow across the east end of Hudson Strait in northern Canada. The resulting flood of icebergs into the southern half of the Northern Gyre adjacent to the Gulf Stream converted western Europe’s mild climate to an arctic climate. The collapse event was caused by the last large accumulation of glacial ice in the thick ice dome of Hudson Bay. The accumulation created a pressure gradient that forced an ice stream flow eastward in Hudson Strait. A highly saline sub-glacial lake had formed earlier in the western part of the strait. The ice stream flow entrained saline lake water in a network of channels at the seabed between the lake and the ice dam, melting and extending the network eventually to and beneath the ice dam. This detached much of the ice dam from its frozen bed and caused its catastrophic collapse and the onset of the Younger Dryas in only one year.